Revisiting Risley prism transmit-array antennas using a novel co-design phase correction approach - Matos, S. A.; Fonseca, N. J. G.; Serra, J.; Felício, J. M.; Costa, J. R.; Femandes, C. (2024 IEEE International Symposium on Antennas and Propagation and INC/USNC‐URSI Radio Science Meeting (AP-S/INC-USNC-URSI), 2024)
Mechanical beam steering using two independent axially rotating metasurfaces (Risley Prism configuration) have proved to be a cost-effective solution for millimeter wave (mmW) antennas. Adapting this canonical beam steering concept from optics to mmW using metasurfaces (instead of wedge prisms) allows achieving a greater design flexibility. Many works have explored different ways of encoding the required phase correction. All of them implicitly implement three functionalities: i) beam collimation (i.e., plane wave conversion); ii) 1D beam tilting along a given axis; iii) 1D beam tilting along a second direction, the two tilting direction being set to produce the prescribed beam pointing direction. Conventionally, steps i) and ii) are solved by the first operating metasurface, which sets the phase delay profile of the second metasurface. Recently, the authors have shown an alternative approach where the beam collimation is performed by the combined effect of the two metasurfaces. Using 3D-printed perforated slabs we have previously demonstrated that this generalized approach is effective for the reduction of the side lobe level in the conventional case. In this communication, we will present alternative implementations of this concept to demonstrate the wider reach of our findings.